Prevalensi gambaran klinis kandidiasis oral pada penderita sindrom sjogren (Laporan Penelitian) - Andrian Nova Fitri; Helen Priscilla Margono (Jurnal Kedokteran Gigi Terpadu, 2022)
Background: Sjogren syndrome is a disorder of immunity system which affect exocrine gland, such as salivary gland. It causes sjogren syndrome patients generally have xerostomia as a major complaint, this condition often causes various problems in oral cavity one of them is oral candidiasis. Objective: To assess prevalence of oral candidiasis manifestation in sjogren syndrome patients Method: The research was conducted using the scoping review method in accordance with the PRISMA guidelines. Search is done by using boolean search strategy on three electronic database which are PubMed, Wiley Online Library, and Google Scholar. Result: There are 16 journals reporting manifestation of oral candidiasis in sjogren syndrome patients. Types of oral candidiasis that can be found in sjogren syndrome patients are angular cheilitis, denture stomatitis, erythematous candidiasis, pseudomembranous candidiasis, and median rhomboid glossitis. Conclusion: Oral candidiasis is found more often in sjogren syndrome patients than in healthy subjects due to hyposalivation and xerostomia. Especially angular cheilitis, denture stomatitis, and erythematous candidiasis.